Behavior analysis of fragmental rocks during tunnel excavation using a large-scale 2-D loading apparatus - Roh, Yong Eun; Park, Hyungbin; Baek, Munkyeong; Chang, Ilhan (Geomechanics and Engineering, 2025)
In Korea, most people live in metropolitan areas. Social infrastructure is concentrated in a small area based on the demands of many people. The development of underground space in urban areas using deep tunnels for roads, railways, subways, communication facilities, and waterway facilities is expanding. This underground space is composed of weathered rock ground with geological joints, and many tunnels have been excavated in such ground. The effect of discontinuity on the behavior of the tunnel must be considered during the design and construction stages. Therefore, in this study, a ground model with three dip angles was created using concrete blocks to analyze the relaxation behavior of the surrounding ground when excavating a tunnel in a rock mass with joints. In addition, a trapdoor tester capable of creating linear and nonlinear settlement was manufactured, and the stress distribution and settlement occurrence tendency of the tunnel top and surrounding ground were analyzed when different settlement shapes occurred. The experimental results showed that the behavior of the top of the trapdoor and the surrounding ground varied depending on the displacement shape of the trapdoor and the inclination of the joint surface of the rock. The results of this experiment suggest a displacement shape that is advantageous to the arching effect depending on the inclination of the joint surface of the upper ground during tunnel excavation. In addition, the loosened ground zone of the upper ground can be identified by considering the friction angle of the rock and the dip angle during excavation.
Keywords: Behavior analysis; Dip angle; Fragmental rock; Joint angle; Joint surfaces; Load transfer; Nonlinear deformations; Trapdoor; Tunnel excavation; Underground space; fragmental rocks; joint angle; load transfer; non-linear deformation; trapdoor; tunnel excavation